Strategic Renewal in Times of Environmental Scarcity. Issue 3 (June 2016) - Schmitt, Achim; Barker, Vincent L.; Raisch, Sebastian; Whetten, David
Abstract : While research on strategic renewal is burgeoning, little attention has been paid to the role of renewal in contexts marked by environmental scarcity. Drawing on the population ecology and strategic choice literatures, this paper theoretically explores firms' renewal journeys under distinct environmental scarcity situations, and discusses how managerial perceptions and interpretations shape their strategic renewal behaviors. The resulting conceptual framework refines prior co-evolutionary perspectives of strategic renewal by showing that the nature of firms' renewal activities varies with the type of environmental scarcity they face. Further, we argue that varying CEO perceptions and interpretations can cause firms within the same industry context to adopt entirely different renewal journeys. Our theoretical framework responds to prior calls for more rigorous theory-building regarding strategic renewal by integrating the population ecology and strategic choice perspectives.